Peningkatan Persepsi Manajer tentang Conscientiousness, Employee Well-Being, dan Intention to Stay untuk Menurunkan Turnover Karyawan di Rumah Sakit X: Peningkatan Persepsi Manajer tentang Conscientiousness, Employee Well-Being, dan Intention to Stay untuk Menurunkan Turnover Karyawan - Achmad Djunawan; Anisful Lailil Munawaroh; Emilia Indahyati; M Risya Rizki; Anif Prasetyorini; WD. Yuni M. Usa (Jurnal Abdimas Jatibara, 2026)
Employee turnover remains a major challenge for hospitals because it can affect service quality, organizational stability, and operational efficiency. Strengthening employee conscientiousness, employee well-being, and intention to stay is considered an important strategy to support employee retention and reduce turnover risk. The objectives of this community service activity aimed to improve participants’ perceptions and understanding of conscientiousness, employee well-being, and intention to stay among managerial personnel at X Hospital, Surabaya. The methods of the activity were conducted through interactive socialization, dissemination, and discussions. Participants consisted of six managerial members. Evaluation used participation and the perception of members. Pretest and posttest questionnaires through Google Forms were used to assess the perception. Data were analyzed using the Kolmogorov–Smirnov normality test and paired t-test to assess differences in participants’ perceptions before and after the socialization. The results showed an increase in the mean scores of all measured indicators after the educational intervention. The mean pretest score increased from 9.067 to 9.667 in the posttest. However, the paired t-test indicated that the difference was not statistically significant (p = 0.314). The findings suggested that participants already had a high level of understanding before the intervention, while the activity reinforced and enriched their existing knowledge. The community service activity was successfully implemented and contributed to strengthening participants’ understanding of conscientiousness, employee well-being, and intention to stay. Continuous educational programs are recommended to support employee retention strategies and reduce turnover in hospitals.